Master of Institutional Governance and Leadership (MIGL) - Kabale University (Kabale University, 2022)
The programme is aimed at the all-round education, acquiring academic expertise and competences that are typical of functioning in the domain of governance, leadership, administration and management in the public sector and other sectors.